Predation affects alarm call usage in female Diana monkeys (Cercopithecus diana diana) - Stephan, Claudia; Zuberbühler, Klaus (My University, 2014)
Diana monkeys produce acoustically distinct calls to a number of external events, including different types of predators. In a previous study, we found population-wide differences in male alarm call production in Taï Forest, Ivory Coast, and on Tiwai Island, Sierra Leone, mostly likely originating from differences in predator experience. In Taï Forest, leopards (Panthera pardus) are common but on Tiwai Island they have been absent for decades, while the predation pressure from crowned eagles (Stephanoaetus coronatus) has been similar. To further evaluate the impact of predator experience, we here analyse the vocal behaviour of female Diana monkeys in both habitats. Female Diana monkeys produce predator-specific alarm calls, alert calls and contact calls in response to predators, suggesting that their calls serve in a broader range of functions compared to males. Results showed that females produced the same call types at both sites, despite the differences in predator fauna. Regarding call usage, leopard alarm calls were extremely rare on Tiwai Island, but not in Taï Forest, whereas we found no differences in eagle alarm call production. When comparing response latencies, Tiwai females were slower to respond to both predators compared to Taï females. Finally, we found no habitat-specific acoustic differences in the alert and predator-specific alarm calls, but significant differences in frequency-based parameters of contact calls. Overall, our results suggest that ontogenetic experience can affect primate vocal behaviour in both usage and acoustic structure but that the way in which particular call types are affected may be closely linked to function.
Keywords: Vocal flexibility; Vocal development; Predation; Predator-specific alarmcalls; Predator absence